2008
DOI: 10.1002/ejic.200800477
|View full text |Cite
|
Sign up to set email alerts
|

Checking the Route to Cluster Helicates

Abstract: The aim of the work described here was to test the general applicability of our recently reported route to cluster helicates and to carry out a systematic study to relate the structural and coordinative properties of the organic strands with the microarchitectures of the resulting cluster helicates. Nine new ZnII, CuI and AgI complexes were prepared from three Schiff base ligands [H2La: bis(4‐methyl‐3‐thiosemicarbazone)‐2,6‐diacetylpyridine; H2Lb: bis(4‐methyl‐3‐thiosemicarbazone)‐2,6‐diacetylbenzene; H2Lc: bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 84 publications
(36 reference statements)
2
28
0
Order By: Relevance
“…With the aim of increasing the denticity of the ligands, bisthiosemicarbazones derived from 2,6-diacetyl pyridine were also synthesized and some metal complexes were electrochemically obtained. This is the case for the electrolysis of an acetonitrile solution of bis- [131]. As in the case of the Cu(I) complexes, no significant differences between the Ag(I) complexes with similar ligands (with phenyl or pyridine spacer)…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…With the aim of increasing the denticity of the ligands, bisthiosemicarbazones derived from 2,6-diacetyl pyridine were also synthesized and some metal complexes were electrochemically obtained. This is the case for the electrolysis of an acetonitrile solution of bis- [131]. As in the case of the Cu(I) complexes, no significant differences between the Ag(I) complexes with similar ligands (with phenyl or pyridine spacer)…”
Section: Methodsmentioning
confidence: 84%
“…When an acetonitrile solution of bis(N-ethylthiosemicarbazone)-1,3-diacetylbenzene (H 2 L44b) was electrolyzed with a silver anode, the complex [Ag 4 (L44b) 2 ] was obtained [131].…”
Section: Co(ii) Ni(ii) and Cu(ii) Complexes [M(l42a) 2 ] And [M(l42bmentioning
confidence: 99%
See 1 more Smart Citation
“…Other signals at m / z 790.24 and 1473.58 were observed with low intensity for two bimetallic complexes with two and four strands, respectively [( 2a 2 Ag 2 ) 2+ and ( 2a 4 Ag 2 ) 2+ , Figure S14]. These results revealed that the 3:2 binding stoichiometry for the complex formed by 2a and Ag I ions was also the dominant coordination mode in solution 18b. For the Ag I complex of 3 , no featured peaks were detected, presumably because of the poor solubility of the complex in polar solvents such as acetonitrile and methanol used in the ESI experiments.…”
Section: Resultsmentioning
confidence: 97%
“…Generally hydrazone Schiff bases behave as pentadentate ligands through pyridinic nitrogen, imine nitrogens and carbonylic oxygen atoms and their chelating properties have been investigated for a great number of transition metal ions [1][2][3][4][5][6] and in an important field like the construction of helical complexes with high nuclearity [6]. The Schiff bases derived from functionalized amines give as a result ''bibracchial" ligands with donor groups in two pendant arms which can lead to important changes in the complexation capability of the ligands and can enhance the stability of the metal complexes.…”
Section: Introductionmentioning
confidence: 99%